Answer: The required solution of the given quadratic equation is
x = 3 + √3 and x = 3 - √3.
Step-by-step explanation: We are given to solve the following quadratic equation using quadratic formula :
![x^2-6x+6=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3mx4i9xai6f73no3lucgt18u967qu9di1y.png)
Quadratic formula : The solution of a quadratic equation of the form
is given by
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wpsjul336yk57nz9umgxw6d875oesezks4.png)
For the given quadratic equation (i), we have
a = 1, b = -6 and c = 6.
Therefore, the solution of equation (i) is given by
.
Thus, the required solution of the given quadratic equation is
x = 3 + √3 and x = 3 - √3.